A mirror to humanity: the meaning-making experiences of correctional end-of-life care advocates - Kaushik, Shivani, author; Currin-McCulloch, Jennifer, advisor; Hogan, Michael, committee member; Yoder, Jamie, committee member; Yuma, Paula, committee member (Colorado State University. Libraries, 2023)
The purpose of this study was to explore the mean-making experiences of advocates who strive to implement end-of-life programming in correctional settings. The study included five main exploratory aims: (1) to explore advocates' understanding of end-of-life philosophy; (2) motivating factors of advocates that promote end-of-life caregiving opportunities; (3) barriers to the provision of end-of-life care; (4) how personal, social, and political influences related to correctional end-of-life care shape advocates' meaning-making experiences and; (5) to better inform the general public of this integral need and humane service to combat the stigma related to accessing end-of-life care for incarcerated individuals. Interpretative phenomenological analysis (IPA), a qualitative approach which aims to provide detailed examinations of personal lived experience, was incorporated with English-speaking participants, residing in the United States (U.S.), who are 18 years of age or older and identify as advocates for correctional end-of-life care. Participants were recruited with the assistance of professionals who work within the field of end-of-life care in the United States and non-profit, correctional health care advocacy groups. Advocates participated in a recorded interview, via Zoom or telephone, consisting of 15 semi-structured questions which addressed their knowledge of end-of-life care in corrections, recommendations for policy reform, and the meaning-making experiences derived from advocating for essential care to the terminally ill. Participant responses were transcribed and analyzed by maintaining an idiographic focus and providing verbatim quotes. The results revealed advocates' multifaceted meaning-making experiences in championing for humane end-of-life care in corrections: daunting work as motivation; the people are the joy; this is what I'm meant to do; and being a mirror to humanity. Advocates revealed the pertinent need to eradicate punitive ideals to deliver compassionate care. Narratives underscored the significant bonds with imprisoned people and fellow peers advocating for empathy at the end-of-life. These advocates additionally highlighted their inherent aspirations for social justice and health equity. Moreover, opportunities to showcase and celebrate the compassionate skill-set and productivity of peer-volunteers delivering care to their dying peers in corrections surfaced as emotional and inspiring experiences for advocates. The exploration of the meaning-making experiences of correctional end-of-life care advocates provided a unique perspective into the motivating factors and multifarious challenges of implementing and delivering compassionate care to terminally ill incarcerated people. Advocates offer significant and hidden insights into the dying experience of this marginalized population, while navigating the complexities of correctional health care. The knowledge and vigor of advocates serve as key factors in ameliorating appropriate end-of-life care for a continually punished population. The study emphasizes the fundamental need to assess current models of care available to dying incarcerated individuals in the United States and how advocates' participation can enhance end-of-life care in corrections. Further research must investigate current end-of-life programming in corrections, with an emphasis on the unique roles of those delivering care. The essential voices of correctional end-of-life advocates should be integrated into policy reform which seeks to amend dated and unjust practices impacting dying incarcerated individuals.
Keywords: aging; corrections; interpretative phenomenological analysis; caregiving; advocacy; end-of-life care